Unlocking Real Sector Growth through Sukuk: Regulatory Challenges and Developmental Impacts in Indonesia - Desiana, Desiana; Salsabila, Raddine; Sarmigi, Elex (Faculty of Sharia and Law, UIN Syarif Hidayatullah Jakarta, 2025)
This study explores how sukuk regulations boost investor participation and impact productive sectors in Indonesia. Using a normative juridical approach, it examines relevant laws and literature. Findings show that regulations from OJK, DSN-MUI, and the Ministry of Finance have supported sukuk market growth. However, complex issuance procedures and limited secondary market liquidity remain key challenges. Despite this, sukuk has contributed to infrastructure, green energy projects, and MSME development. The study recommends simplifying regulations, enhancing market liquidity, and innovating sukuk products to strengthen their role in driving sustainable economic growth. Abstrak:Penelitian ini mengkaji efektivitas regulasi sukuk dalam mendorong partisipasi investor dan dampak ekonominya pada sektor produktif di Indonesia. Dengan pendekatan yuridis normatif, penelitian ini menelaah peraturan dan literatur terkait. Studi ini menunjukkan bahwa regulasi dari OJK, DSN-MUI, dan Kementerian Keuangan mendukung pertumbuhan pasar sukuk. Namun, prosedur penerbitan yang kompleks dan terbatasnya likuiditas pasar sekunder masih menjadi tantangan utama. Meski demikian, sukuk telah berkontribusi pada pembangunan infrastruktur, proyek energi hijau, dan pengembangan UMKM. Studi ini merekomendasikan penyederhanaan regulasi, peningkatan likuiditas pasar, dan inovasi produk sukuk untuk memperkuat perannya dalam mendorong pertumbuhan ekonomi berkelanjutan.